AKIBAT HUKUM PERJANJIAN KERJA ANTARA PIHAK PENGUSAHA DENGAN PIHAK PEKERJA DITINJAU DARI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Yulia Handari, Putu Ayu; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum, 2013)
Employment agreement between employer party and employee party is made by using fixed agreement, so within the process of making agreement is not through pre-contract steps as it is normally initiated with negotiation process between employee party and employer party and also this agreement is made under hand. Although employment agreement is made in term of fixed agreement and under hand, but this agreement keeps on the effort to refer to regulation listed in Article 1320 Civil Act and Article 52 point 1 of Indonesian Republic Regulation no. 13 of 2003 as it is the legal main condition for an agreement and also as the basic law of employment agreement. The legal consequence of employment agreement which is made between employer party and employee party that the sanction assigned to employees who violate the regulation agreed in this employment agreement, namely: If employer or employee terminate employment agreement within certain period prior ended, so the party who terminates this employment agreement must pay compensation to other party at the rest salary of the worker until the period or the worker should finish his contract period, except termination of employment agreement die to serous force/fault from employee. Any dispute taken place as consequence of this employment agreement should be settled by both parties through Registration Office of District Court Denpasar.
Keywords: Employment Agreement, Employer, Employee